Trypanothione Reductase High-Throughput Screening Campaign Identifies Novel Classes of Inhibitors with Antiparasitic Activity - Holloway, Georgina A. (American Society for Microbiology (ASM), 2009)
High-throughput screening of 100,000 lead-like compounds led to the identification of nine novel chemical classes of trypanothione reductase (TR) inhibitors worthy of further investigation. Hits from five of these chemical classes have been developed further through different combinations of preliminary structure-activity relationship rate probing and assessment of antiparasitic activity, cytotoxicity, and chemical and in vitro metabolic properties. This has led to the identification of novel TR inhibitor chemotypes that are drug-like and display antiparasitic activity. For one class, a series of analogues have displayed a correlation between TR inhibition and antiparasitic activity. This paper explores the process of identifying, investigating, and evaluating a series of hits from a high-throughput screening campaign.